2018
DOI: 10.15405/epsbs.2018.07.02.65
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Finance And Speculative Behavior Of Investors: Evidence From Saudi Stock Market

Abstract: This study examines the profile of individual stock traders in Saudi stock market and attempts to determine the behavioral finance factors affecting the speculative behavior of investors as well as to discover the strongest predictors. Using questionnaire survey method, 130 individual traders in Saudi stock market were identified for this study. The survey is carried out in the biggest brokerage firms in Dammam, Riyadh, and Jeddah. It appears that more than 50% of the individual stock traders are in the age gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
2
6
0
Order By: Relevance
“…The significance value is 0.001, which means that heuristic variable has a significant positive impact on portfolio construction and performance satisfaction level. This finding is consistent with the results from the study of Chen et al (2007), Chandra and Kumar (2012), Tekce et al (2016) and Alsedrah and Ahmed (2017), who found heuristics factors to affect investors behavior. In addition, the results of Khan's et al (2017) study led to the conclusion that the presence of heuristic bias like representativeness and overconfidence deteriorates financial behavior.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The significance value is 0.001, which means that heuristic variable has a significant positive impact on portfolio construction and performance satisfaction level. This finding is consistent with the results from the study of Chen et al (2007), Chandra and Kumar (2012), Tekce et al (2016) and Alsedrah and Ahmed (2017), who found heuristics factors to affect investors behavior. In addition, the results of Khan's et al (2017) study led to the conclusion that the presence of heuristic bias like representativeness and overconfidence deteriorates financial behavior.…”
Section: Resultssupporting
confidence: 92%
“…In another study, Chang et al (2019) explained that investors tend to anchor on day prices in valuating ex-distribution stocks, resulting in a positive association between ex-day returns and adjustment factors. A recent study which was published by Alsedrah and Ahmed (2017) examined the profile of 130 individual stock traders in Saudi Stock Market and attempts to determine the behavioral finance factors affecting the speculative behavior of investors. Anchoring appears to be the main predictor of speculative behavior, followed by confirmation, representativeness and overconfidence.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Matoussi and Mostafa (2016) examined the behavioral biases that affect Saudi investors and confirmed that Saudi investors' behavior is characterized by overconfidence, low opportunism, and sensitivity to rumors. This result is also supported by Alsedrah and Ahmed (2017), that anchoring, confirmation, representativeness and overconfidence heuristics have a significant relationship with speculative behavior. Canepa and Ibnrubbian (2014) investigated influence of Islamic tenets on the stock market, and found that they have a significant effect on investors' decisions.…”
Section: Introductionsupporting
confidence: 66%
“…Recent work on determinants of investor's behavior can be classified in two segments. Segment one focusses on investor bias and overreaction (Matoussi and Mostafa, 2016;Alsedrah and Ahmed, 2017;Alsabban and Alarfaj, 2020). Second segment explores the factors that influence individual investor's behavior (Jagongo and Mutswenje, 2014;Al-Tamimi, 2006;Merikas et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…GCC markets are considered in the finance literature due to their importance to the global economy (Alnori et al, 2021;Bugshan et al, 2021). Some studies investigated the behavioural factors related to individual investors in the GCC setting (Abdullah and Hilu, 2015;Alsedrah and Ahmed, 2017;Khawaja and Alharbi, 2021;Matoussi and Mostafa, 2016). For instance, Matoussi and Mostafa (2016) examined the behavioural biases that influence Saudi investors in the main stock exchange (TASI).…”
Section: Individual Investors' Behavioural Factors In the Gcc Marketsmentioning
confidence: 99%